2006
DOI: 10.1007/s00248-006-9129-6
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Endophytic Streptomycetes from Nothofagus spp. and Other Plants in Patagonia

Abstract: Endophytic streptomycetes have been isolated and characterized from several species of Nothofagus and other plants growing in the southern reaches of Patagonia. No endophytic streptomycete was obtained from any plant species studied in Northern Patagonia. However, from Southern Patagonia, biologically active Streptomyces spp. from several plant species were isolated. Each isolate, as studied by scanning electron microscopy (SEM), has small hyphae, some produce typical barrel-shaped spores in culture and each h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…Actinobacterial endophytes of terrestrial and marine plants are considered potential sources of novel secondary metabolites (Bascom-Slack et al, 2009;Castillo et al, 2003Castillo et al, , 2007Liu et al, 2014;Strobel et al, 2004). Most of the Streptomyces strains isolated in this study showed antimicrobial activity against a broad range of indicator organisms, which usually cause serious losses in agricultural production.…”
Section: Discussionmentioning
confidence: 89%
“…Actinobacterial endophytes of terrestrial and marine plants are considered potential sources of novel secondary metabolites (Bascom-Slack et al, 2009;Castillo et al, 2003Castillo et al, , 2007Liu et al, 2014;Strobel et al, 2004). Most of the Streptomyces strains isolated in this study showed antimicrobial activity against a broad range of indicator organisms, which usually cause serious losses in agricultural production.…”
Section: Discussionmentioning
confidence: 89%
“…One fungus, designated CR-12, was recovered from Pteromischum sp. and when grown on potato dextrose agar (PDA) was initially shown to have antimycotic activity by virtue of a bioassay test (Castillo et al, 2007). The organism was examined for its morphological and spore-forming features as described below for taxonomic purposes.…”
Section: Methodsmentioning
confidence: 99%
“…were the predominant species, and Microbispora, Micromonospora, Nocardioides, Nocardia, and Streptosporangium were the common genera. Endophytic actinobacteria have been demonstrated to improve and promote the growth of host plants as well as to reduce disease symptoms caused by plant pathogens through various mechanisms, including the production of secondary metabolites, which are used in direct antagonism against pests and diseases (9,10,12), changes in host physiology (42), and the induction of systemic acquired resistance in plants (15). Another significant function found for these actinobacteria was antibiotic activity, suggesting that endophytic actinobacteria can be an interesting source for bioprospecting.…”
mentioning
confidence: 99%